Resistance & Recovery in the #MeToo Era. Issue 3 (2nd October 2021) - Richmond, Kate; Johnson, Nicole L.
Abstract: This special issue aims to amplify the voices of those who were and continue to be at the frontlines resisting and responding to sexual violence. In order to frame this special issue, we first outline the current socio-political landscape, including increased visibility of movements such as #NoMore, #TimesUp, and most notably #MeToo, and the public showcase of accused perpetrators becoming elected to the highest offices in the United States (e.g., Brett Kavanaugh's election to the Supreme Court, Donald Trump's election to the Presidency). We offer note to how this political landscape has impacted survivors and therapists, alike. We then provide a critique of the silencing of survivors who are marginalized (e.g., women of color, trans, and queer survivors) within the current movements and offer recommendations for how to center their experiences through an intersectional approach. Finally, we explore the role of technology and digital feminisms on survivor's experience and its influence on therapist and therapeutic interventions.